Implementasi Slow Sand Filter (SSF) untuk Meningkatkan Kualitas Air Bersih di SMAN 1 Manuhing Raya - Tety Wahyuningsih Manurung; Mokhamat Arifien; Indra Dwi Kusuma; Joy Angel Aria Suma; Risfiah Ruli Cahyani; Muh. Supwatul Hakim; Yuniarta Basani (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
SMAN 1 Manuhing Raya, located in Tehang Village, Manuhing Raya District, Gunung Mas Regency, Central Kalimantan, relies primarily on water from a nearby river. However, the water quality is substandard; its cloudy appearance and acidity pose health risks to students and staff, disrupting the teaching and learning process. To address this, a Slow Sand Filter (SSF) water purification system was implemented to ensure the availability of clean water at the school. The implementation involved two stages: socialization and practical training on SSF construction and maintenance. Students responded positively to the socialization and demonstrated understanding of the SSF assembly and upkeep. The SSF effectively reduced water turbidity from 8.00 to 6.00, clarified its color from yellowish to clear, and increased its pH from 6.4 to 7.6. In conclusion, this initiative successfully provided clean water to the SMAN 1 Manuhing Raya community and equipped students with knowledge about SSF construction and maintenance, applicable in their own living environments.